2013
DOI: 10.1128/jvi.01156-13
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Megakaryocyte Development in the Bone Marrow Underlies Dengue Virus-Induced Thrombocytopenia in Humanized Mice

Abstract: A characteristic clinical feature of dengue virus infection is thrombocytopenia, though its underlying mechanism is not definitively determined. By adoptive transfer of human CD34؉ fetal liver cells into immunodeficient mice, we have constructed humanized mice with significant levels of human platelets, monocytes/macrophages, and hepatocytes. Infection of these mice with both lab-adapted and clinical strains of dengue virus induces characteristic human hematological changes, including transient leukopenia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 29 publications
7
75
1
Order By: Relevance
“…Consistent with previous studies (21,32), we also observed a significant decrease in circulating total platelets, i.e., thrombocytopenia, another hallmark of DENV infection in humans. Thrombocytopenia is fre- quently observed among dengue fever patients, and two mechanisms have been proposed to explain it: antibody-mediated depletion of platelets from peripheral blood (45)(46)(47)(48)(49) and deficient platelet production by megakaryocytes in the bone marrow (25,50). The latter hypothesis is supported by a study that demonstrated that human megakaryocytes from the bone marrow were highly permissive for DENV infection in vitro, suggesting that megakaryocytes may also be targeted in vivo, thus providing a plausible mechanism for thrombocytopenia during acute infection in humans (50).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies (21,32), we also observed a significant decrease in circulating total platelets, i.e., thrombocytopenia, another hallmark of DENV infection in humans. Thrombocytopenia is fre- quently observed among dengue fever patients, and two mechanisms have been proposed to explain it: antibody-mediated depletion of platelets from peripheral blood (45)(46)(47)(48)(49) and deficient platelet production by megakaryocytes in the bone marrow (25,50). The latter hypothesis is supported by a study that demonstrated that human megakaryocytes from the bone marrow were highly permissive for DENV infection in vitro, suggesting that megakaryocytes may also be targeted in vivo, thus providing a plausible mechanism for thrombocytopenia during acute infection in humans (50).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, its efficiency remains low (Mikkelsen et al, 2008;Pasque et al, 2012;Gaspar-Maia et al, 2013;Sridharan et al, 2013;Nashun et al, 2015), the extreme stability of adult somatic cell epigenetic signature makes iPSCs prone to errors (Plath and Lowry, 2011), and the use of DNA constructs and the subsequent possibility of exogenous sequence integration preclude their clinical use for safety concerns (Stadtfeld et al, 2008;Kim et al, 2009;Zhou and Freed, 2009;Seki et al, 2010). In order to circumvent these limits, smallmolecule compounds have been used to modulate the epigenetic state by inhibiting and/or activating, in a reversible way, specific signaling pathways (Huangfu et al, 2008;Ichida et al, 2009;Li et al, 2011;Hou et al, 2013).…”
Section: Erasing Of "Epigenetic Memory"mentioning
confidence: 99%
“…Dengue virus infection was performed by intraperitoneal, subcutaneous of intravenous injection into HIS mice [62][63][64][65][66]. In most instances dengue serotype 2 viruses were used.…”
Section: Flavivirus Infections (Dengue Virus Hcv)mentioning
confidence: 99%
“…Dengue virus infection was performed by intraperitoneal, subcutaneous of intravenous injection into HIS mice [62][63][64][65][66]. In most instances dengue serotype however, is dengue hemorrhagic fever after heterologous infection with another dengue virus serotype and it is thought that heterologous antibodies enhance infection by the second phenotype to cause this severe disease [67].…”
Section: Flavivirus Infections (Dengue Virus Hcv)mentioning
confidence: 99%